Nature-Based Solutions - Dimitrakopoulos, Panayiotis G.; Pagnotta, Mario; Scholz, Miklas; Noorani, Arshiya (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
'Nature-based solutions' (NbS) is an umbrella term for ecosystem-based approaches. It focuses on actions and policies that are in harmony with natural principles to achieve development goals and addressing challenges, while benefitting human livelihoods and the environment. The reprint contains empirical studies and systematic reviews regarding, inter alia, natural and green infrastructures, ecosystem-based management approaches, ecosystem and biodiversity conservation, ecosystem-based adaptation and climate change adaptation, and nature-based recreational activities.